2006
DOI: 10.1097/01.tp.0000228872.89572.d3
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Pediatric En Bloc Renal Allografts Over Living Donor Kidneys: A Long-term Functional Study

Abstract: Early postoperative graft thrombosis remain a challenge with pediatric en bloc renal transplants, but once the allografts survive early postoperative course, they provide better long-term function than living donor kidney transplants. In order to alleviate burden on waiting list, pediatric en bloc kidneys should be transplanted more often when available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 24 publications
5
69
2
1
Order By: Relevance
“…Based on animal studies and experience from clinical settings, en bloc grafts increase in size rapidly to adapt to the host environment [4,[10][11][12][13]. This was supported by our study, in which eGFR was significantly higher as far out as 5 years after transplantation, for recipients of en bloc kidneys compared with recipients of standard deceased donor kidneys.…”
Section: Other Benefits Of En Bloc Transplantssupporting
confidence: 74%
“…Based on animal studies and experience from clinical settings, en bloc grafts increase in size rapidly to adapt to the host environment [4,[10][11][12][13]. This was supported by our study, in which eGFR was significantly higher as far out as 5 years after transplantation, for recipients of en bloc kidneys compared with recipients of standard deceased donor kidneys.…”
Section: Other Benefits Of En Bloc Transplantssupporting
confidence: 74%
“…The graft survival of en block kidney transplants has been shown to be similar to that of adult deceased-donor kidneys (3) and probably even live-donor kidneys (13). As a result, pediatric en block kidneys are routinely transplanted together into one recipient.…”
Section: Discussionmentioning
confidence: 99%
“…The graft survival of en bloc kidneys has been at least comparable to standard deceased donor kidneys [4,[8][9][10][11][12]. Some studies in fact have shown superior outcomes with en bloc transplants compared to standard deceased donor and even live donor transplants [13][14][15]. In a recent study from France, researchers compared the graft survival among recipients of en bloc grafts (mean donor age of 15 months) to those receiving standard donor grafts (mean donor age of 38 years); those who received en bloc kidneys fared better than their counterparts, with a 10 year survival of 74% compared to 58% [14].…”
Section: En Bloc Renal Transplantation Is a Viable And Safe Option Tomentioning
confidence: 99%
“…Reduce nephron mass renders the graft more prone to early hyper-filtration injury; en bloc grafts with twice the number of nephrons and higher volume may mitigate this risk [17,18]. Based on animal studies and experience from clinical settings, en bloc grafts but not ideal single kidney donor grafts, increase in size rapidly to adapt to the host environment [5,15,[19][20][21].…”
Section: Advantages Of En Bloc Over Solitary Grafts From Young or Idementioning
confidence: 99%